Can China Continue Feeding Itself ? : The Impact of Climate Change On Agriculture - Wang, Jinxia (The World Bank, 2008)
Several studies addressing the supply and demand for food in China suggest that the nation can largely meet its needs in the coming decades. However, these studies do not consider the effects of climate change. This paper examines whether near future expected changes in climate are likely to alter this picture. The authors analyze the effect of temperature and precipitation on net crop revenues using a cross section consisting of both rainfed and irrigated farms. Based on survey data from 8,405 households across 28 provinces, the results of the Ricardian analysis demonstrate that global warming is likely to be harmful to China but the impacts are likely to be very different in each region. The mid latitude region of China may benefit from warming but the southern and northern regions are likely to be damaged by warming. More precipitation is beneficial to Chinese farmers except in the wet southeast. Irrigated and rainfed farmers have similar responses to precipitation but not to temperature. Warmer temperatures may benefit irrigated farms but they are likely to harm rainfed farms. Finally, seasonal effects vary and are offsetting. Although we were able to measure the direct effect of precipitation and temperature, we could not capture the effects of change in water flow which will be very important in China. Can China continue feeding itself if climate changes? Based on the empirical results, the likely gains realized by some farmers will nearly offset the losses that will occur to other farmers in China. If future climate scenarios lead to significant reductions in water, there may be large damages not addressed in this study